Shockwave structures in real gases: transition between shock interactions of different types in nonuniqueness solution regions - Tarnavsky, G.A.; Tarnavsky, A.G. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2004)
The physical aspects of nonuniqueness for the shockwave structures arising in super- and hypersonic flows are considered. The thermodynamic conditions specifying the regions of double solution are analyzed. Possible scripts for variation of gas dynamic flow pictures near the boundary of «Mach/regular reflection« transition are investigated